Construcción de un modelo estadístico para la gestión de la cartera de cobro del Servicio de Rentas Internas Zonal 8 - Bedor Vargas, Deyton Darío (2015)
Collection management as fundamental element of the collect function of the Direction Zonal 8 of the Ecuadorian Internal Revenue Services, is responsible for carrying out many activities for recovery portfolio receivable, these are designed to reduce the amount of the portfolio and recovery resources (money) that belongs to the State, in that sense, several authors have shown that the collection risk analysis by the statistical models allows high levels of efficiency and quality in the collection management, since the measurement of payment probability reduces uncertainty and implements strategies and mechanisms for an efficient, faster and timely management of portfolios receivable. For these reasons, the aim of this research is to build a statistical model that measures no-payment risk to the Collection Department of Zonal 8 or Ecuadorian Internal Revenue Service, using a logistic regression logit with one dependent binary variable that reflects whether the obligation is paid or not, it will being explained by twenty independent variables, based on not-prescribed portfolio receivable and other information available in the Tax Administration of Ecuador. With 95 % confidence and according to the statistical validations, the proposed and estimated model classifies properly to 87.26 % of Zonal 8 taxpayers, and this research also proposes an alternative way to manage its portfolio.